2004
DOI: 10.1103/physreve.70.051805
|View full text |Cite
|
Sign up to set email alerts
|

Thickness dependence of structural relaxation in spin-cast, glassy polymer thin films

Abstract: The isothermal structural relaxation of glassy, spin-cast polymer thin films has been investigated. Specifically, the thickness h of freshly cast poly(methyl methacrylate) thin films was measured over time using spectroscopic ellipsometry. The spin-cast films exhibit a gradual decrease in thickness, which is attributed to structural relaxation of the glass combined with simultaneous solvent loss. In all cases, h was found to be greater than the equilibrium thickness h ϱ , which is obtained by cooling slowly fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 35 publications
(62 reference statements)
5
57
1
Order By: Relevance
“…Toluene was used as the solvent for PMMA, and tetrahydrofuran was used for PAA-b-PMMA. Then the films were annealed in a vacuum oven at 120 ºC for two hours to remove residual solvent and to allow the films to relax (Richardson et al 2004). This technique yielded smooth films with thicknesses ranging between 15 and 25 nm.…”
Section: Surface Preparationmentioning
confidence: 99%
“…Toluene was used as the solvent for PMMA, and tetrahydrofuran was used for PAA-b-PMMA. Then the films were annealed in a vacuum oven at 120 ºC for two hours to remove residual solvent and to allow the films to relax (Richardson et al 2004). This technique yielded smooth films with thicknesses ranging between 15 and 25 nm.…”
Section: Surface Preparationmentioning
confidence: 99%
“…Solvent loss and the accompanying structural relaxation are exceedingly slow in glassy films at sub-T g temperatures. 37 In the preparation of the diodes used here, the PTAA was annealed above its T g to allow any solvent trapped inside the film to escape. To examine the solvent loss from the PTAA films, TGA was employed ͓Fig.…”
Section: -5mentioning
confidence: 99%
“…For an amorphous polymer such as PMMA, with a high glass transition temperature, it was shown that a glassy material is obtained once the solvent fraction in the film is less than 0.19, and the formation of the glass will considerably decrease the evaporation rate of the solvent. 44,45 The amount of retained solvent in different cast films was studied by several groups. 44,45,[47][48][49] García-Turiel and Jé rô me 47 used gas chromatography to study solvent retention in PS films spin cast from toluene.…”
Section: Related Research On Glass Transition Temperature In Thin Filmsmentioning
confidence: 99%
“…44,45 The amount of retained solvent in different cast films was studied by several groups. 44,45,[47][48][49] García-Turiel and Jé rô me 47 used gas chromatography to study solvent retention in PS films spin cast from toluene. They concluded that while in thick films, there are only a few percent of solvents left after annealing at a temperature above the glass transition temperature, the amount of retained solvent can be much higher in thin films.…”
Section: Related Research On Glass Transition Temperature In Thin Filmsmentioning
confidence: 99%